The heat transfer coefficient on film cooled surfaces - Ammari, H.D. (1989)
A systematic investigation of the effects of coolant-to-mainstream density ratio and mainstream acceleration on the heat transfer following injection through a row of holes in a flat plate into a turbulent boundary layer is described. A mass transfer technique was employed which uses a swollen polymer surface and laser holographic interferometry. The constant concentration of the test surface simulated isothermal conditions. Density ratios in excess of unity, representative of gas turbine operating conditions, were obtained using foreign gas injection into mainstream air. The experimental technique was validated for such measurements. The cooling film heat transfer coefficient was measured for a range of blowing configurations and flow conditions; the holes were spaced at three diameter intervals and inclined at 35° or 90° to the mainstream, and the ranges of the other pertinent test parameters covered were, 0.5 5 blowing rate 5 2.0, 1.0 5 density ratio S 1.52, and 0.0 S acceleration parameter S 5x 10'. However, the tests with mainstream acceleration were performed with 35° injection only. The heat transfer coefficient was found to be increased by injection, and with the blowing rate for both 35° and 90° injection. Close to the injection site, normal blowing produced higher heat transfer coefficients than angled blowing, but gave lower coefficients far downstream. There were large differences in behaviour between the two injection angles with varying density ratio. For normal injection, the heat transfer coefficient at a fixed blowing rate was insensitive to the variation of density ratio, whereas for 35° injection strong dependence was observed, an increase in the density ratio leading to a decrease in the coefficient. Similar behaviour for the inclined injection case was also found in the presence of strong favourable pressure gradient. As mainstream acceleration acts to suppress injection induced turbulence, the heat transfer coefficient under the film with and without density ratio was found to decrease in the presence of mainstream acceleration relative to that in absence of acceleration. The heat transfer coefficient was observed to relate to the acceleration parameter in an approximately linear manner, an increase in the acceleration resulting in a decrease in the coefficient. For normal injection, good scaling of the heat transfer coefficient including density ratios was achieved with the blowing parameter. For 35° injection, the coolant to mainstream velocity ratio was seen to scale the data best. Correlations for the heat transfer data using these scaling parameters. With these correlations data obtained at density ratios not representative of gas turbine practice can be adapted for design calculations. The predictions of a computational fluid dynamics general purpose program called PHOENICS were tested against the present measurements and those of others. In general, the computed results of film cooling effectiveness agreed reasonably well with available experimental data. The ability to predict the heat transfer coefficient associated with film cooling was satisfactory for normal injection, but not as satisfactory for injection through 35° holes.